Pelatihan Entrepreneurship Santri Putri Tahfidzil Qur’an Dengan Memproduksi Serbuk Jamu Kesehatan Di Pondok Pesantren Tahfidzil Qur’an Desa Podorejo Sumbergempol - Lisa Tri Wulandari (LP3M IAIFA Kediri, 2021)
The social environment of today's society is very concerned about the declining economic conditions causing many problems that have arisen, active and innovative activities are needed, especially in the field of entrepreneurship which has recently soared and developed rapidly. The existence of this makes a demand for all educational institutions, especially in the world of Islamic boarding schools to develop and direct, grow and form active, innovative and creative entrepreneurial souls in students who aim to provide skills and knowledge for future life. In the training conducted by researchers at the Tahfidzil Qur'an Islamic Boarding School in Ngadirogo Hamlet, Podorejo Village, Sumbergempol District, Tulungagung Regency, this was raised by good cooperation and communication between researchers and the local community and caregivers and the female students of the Tahfidzil Qur'an Islamic Boarding School. The active participation of the students as well as the local community plays a very important role in the continuity and success of the program. The students are equipped with knowledge and knowledge about the world of entrepreneurship and the importance of entrepreneurship, as an effort to prepare skilled, creative and innovative human beings. Cultivate your potential and abilities in your field.